2010
DOI: 10.1097/ccm.0b013e3181b9ecea
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vancomycin plus rifampicin in the treatment of nosocomial methicillin-resistant Staphylococcus aureus pneumonia*

Abstract: Vancomycin plus rifampicin seems to be more effective than vancomycin alone in the treatment of nosocomial methicillin-resistant Staphylococcus aureus pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 33 publications
2
43
1
3
Order By: Relevance
“…The final response rate observed, about 68.6%, was comparable to the rates seen in clinical trials with hospitalised adults with MRSA infections [10,17,19,21]. However, we found that our high vancomycin MIC group had an early clinical response rate of 35.3%, despite a final clinical response rate at the end of therapy of 64.7%.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The final response rate observed, about 68.6%, was comparable to the rates seen in clinical trials with hospitalised adults with MRSA infections [10,17,19,21]. However, we found that our high vancomycin MIC group had an early clinical response rate of 35.3%, despite a final clinical response rate at the end of therapy of 64.7%.…”
Section: Discussionsupporting
confidence: 80%
“…Patients infected with MRSA isolates with vancomycin MICs [1 lg/mL may respond better to combination therapies or linezolid [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, our model offers an explanation for why the strategy suggested for some antibiotic treatments of pairing a broadly penetrating drug (e.g., rifampicin) with a narrowly penetrating one (e.g., vancomycin) to increase total drug coverage (51) might fail frequently due to the rapid evolution of resistance against the drug with higher penetration (51)(52)(53). It also offers an alternative explanation of why certain drugs are more vulnerable to resistance.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study of 93 patients in South Korea demonstrated that vancomycin plus rifampicin was more effective in the treatment of MRSA nosocomial pneumonia than vancomycin alone [26]. Further clinical data are required to assess whether such therapy has clinical utility.…”
Section: Vancomycinmentioning
confidence: 99%